Transcriptome analysis reveals plant response to colchicine treatment during on chromosome doubling - Kai Zhou (Nature Portfolio, 2017)
Abstract Colchicine was commonly used to artificially double chromosomes while the transcriptome changes in colchicine treated plants has rarely been characterized. To understand the molecular mechanism of colchicine on chromosome doubling, we characterized transcriptome data of diploid orchardgrass root after colchicine treatment. Our results showed that 3381 of differentially expressed genes (DEGs) were mainly affected by water stress, 1258 DEGs that were expressed significantly in sample DacR5tr but not in DacR5ck were considered to be mainly affected by colchicine and combination of water and colchicine. These DEGs mainly regulated by colchicine were enriched to gene ontology (GO) accessions of cation binding, catalytic activity, membrane and transporter activity, and enriched to Kyoto Encyclopedia of Genes and Genome (KEGG) pathways of phenylpropanoid biosynthesis, phenylalanine metabolism, plant hormone signal transduction and starch and sucrose metabolism. Genes related to microtubule, spindle, chromosomal kinetochore, vesicle, cellulose and processes of cytoplasm movement, chromatid segregation, membrane and cell wall development were inhibited by colchicine. Our results revealed that colchicine restrained the microtubules and inhibited gene expression of cytokinesis, which might slow down the cell activity, delay the cell into anaerobic respiration, resulting in apoptosis at late stage, and relieving of waterlogging.